Experimental and Numerical Study of Texture Evolution and Anisotropic Plastic Deformation of Pure Magnesium under Various Strain Paths - Hamad F. Alharbi; Monis Luqman; Ehab El-Danaf; Nabeel H. Alharthi (Advances in Materials Science and Engineering)
The deformation behavior and texture evolution of pure magnesium were investigated during plane strain compression, simple compression, and uniaxial tension at room temperature. The distinctive stages in the measured anisotropic stress-strain responses and numerically computed strain-hardening rates were correlated with texture and deformation mechanisms. More specifically, in plane strain compression and simple compression, the onset of tensile twins and the accompanying texture-hardening effect were associated with the initial high strain-hardening rates observed in specimens loaded in directions perpendicular to the crystallographic c-axis in most of the grains. The subsequent drop in strain-hardening rates in these samples was correlated with the exhaustion of tensile twins and the activation of pyramidal <c+a> slip systems. The falling strain-hardening rates were observed in simple compression and plane strain compression with loading directions parallel to the c-axis where the second pyramidal <c+a> slip systems were the only slip families that can accommodate deformation. For uniaxial tension with the basal plane parallel to the tensile axis, the prismatic and second pyramidal <c+a> slips are the main deformation mechanisms. The predicted relative slip and twin activities from the crystal plasticity simulations clearly showed the effect of texture on the type of activated deformation mechanisms.